2020
DOI: 10.1007/s10389-019-01190-1
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity levels and sedentary time during school hours of 6th-grade girls in Germany

Abstract: Aim Regular physical activity and low levels of sedentary time have positive health effects on youth, and data are needed to base public health recommendations on. Here, findings of device-based physical activity and sedentary time in sixth graders are presented. Data below are presented as mean (SD). Subject and methods Three hundred and eight sixth-grade girls [11.6 (0.6) years] from the CReActivity study in Germany wore accelerometers (ActiGraph GT3X) for 7 consecutive days. Moderate to vigorous physical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
6
1
1
Order By: Relevance
“…However, studies have shown that school time adds significantly to sedentary behaviour among children and adolescents, with as much as three-quarters of school time spent in sedentariness. 25,47 In this study, there was no association between taking after-school lessons and SB. The pervasive nature of media in the lives of adolescents including those in this study may have downplayed the contribution of after-school lessons to sedentariness.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…However, studies have shown that school time adds significantly to sedentary behaviour among children and adolescents, with as much as three-quarters of school time spent in sedentariness. 25,47 In this study, there was no association between taking after-school lessons and SB. The pervasive nature of media in the lives of adolescents including those in this study may have downplayed the contribution of after-school lessons to sedentariness.…”
Section: Discussioncontrasting
confidence: 56%
“…Based on the World Health Organization recommendation of less than two hours per day in a sedentary activity including screen-based and non-screen based behaviours, 2,25 participants were classified as “sedentary” and “non-sedentary”.…”
Section: Methodsmentioning
confidence: 99%
“…According to previous findings in similar conditions, students do not compensate for sedentary behavior either in school or at the weekend [46]. This emphasizes the importance of the development of appropriate conditions for a healthy school lifestyle in all students [47], especially in terms of supporting PA and decreasing sedentary time during school, both in children and adolescents [48][49][50]. A meta-analysis study by Egan et al [50] revealed that school youth spend on average 63% of school time sitting.…”
Section: Discussionmentioning
confidence: 94%
“…Se tuvo en cuenta la valoración de la AF según el día de la semana (entre semana y el fin de semana) y, como parte especial, la AFMV realizada en los distintos patios. La frecuencia de muestreo se estableció en 30 Hz (Sturm, et al, 2021). Para registrar la AF en función de los epochs, los datos se registraban cada 15 segundos (Aadland, et al, 2019).…”
Section: Instrumentosunclassified